Iron-based phosphate sodium ion positive electrode material and preparation method and application thereof
By using precipitation reaction and mechanical mixing technology in the preparation of sodium ion battery positive electrode material, NaxFex-1My(PO4)x-2P2O7/C material was prepared, which solved the problems of low raw material utilization efficiency and high firing loss rate in the existing processes. An efficient and environmentally friendly production process is achieved and electrochemical performance is improved.
Patent Information
- Application Number
- CN202411342166.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-02-11
AI Technical Summary
The existing preparation process of the positive electrode material of the iron-based sodium phosphate ion battery has problems such as low raw material utilization efficiency, high firing loss rate, high cost and environmental pollution.
Preparation of precursors by dissolving iron sources containing +2 and +3 valence states and phosphorus sources containing sodium in deionized water, controlling the pH value, performing precipitation reactions, and mechanically mixing them by ball milling or sand milling, followed by inert Calcining and sintering in an atmosphere to prepare NaxFex-1My(PO4)x-2P2O7/C material.
The raw material utilization rate is improved, the firing loss rate is reduced, the production cost is reduced, and the environmental pollution is reduced. The obtained materials show excellent electrochemical properties in sodium ion batteries and are suitable for industrial production.
Smart Images

Figure CN119409153A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of sodium ion battery electrode materials, and particularly relates to Na x Fe x-1 M y (PO4) x-2 Preparation method and application of P2O7 / C (x=2-5, y=0.002-0.1, M represents a doping element). Background Art
[0002] In the past decade, sodium-ion batteries have been actively explored as a sustainable alternative to lithium-ion batteries for grid-scale energy storage applications. In order to keep the cost as low as possible, people have been paying attention to low-cost polyanion systems. In particular, iron-based phosphate-based sodium-ion batteries have attracted much attention due to their excellent thermal stability and relatively easy preparation process. However, studies have found that this system has low electronic conductivity and Na + The fatal defect of low conductivity. However, there are many ways to solve these problems, including reducing particle size, surface coating and doping. At the same time, the modification of materials is closely related to the preparation process and raw materials. In the traditional method of preparing Na2FeP2O7, FeC2O4 or Fe(NO3)3 is usually used as a precursor. However, this method has the problem of low raw material utilization efficiency, resulting in a large amount of raw materials being lost during the reaction. For example, patent application CN115881948A discloses a preparation method using sodium carbonate as a sodium source, ferrous oxalate dihydrate as an iron source and ammonium dihydrogen phosphate as a phosphorus source. The burn-off rate of the reaction reached 46.5%. This low production efficiency causes waste of resources, increased energy consumption, and increased production costs. In addition, the process releases NH3, CO and a large amount of CO2 with a greenhouse effect during the production process. When Fe(NO3)3 is used as a precursor, nitrogen oxides will be produced, which will have a negative impact on the environment.
[0003] Patent application CN117819512A discloses a method for preparing and applying a sodium iron pyrophosphate positive electrode material. A sodium source, a phosphorus source and a mixed iron source are sequentially added to deionized water, stirred to obtain a suspension, the suspension is sand milled by a sand mill, spray dried to obtain a precursor powder, and the precursor powder is sintered in an inert atmosphere to obtain a sodium iron pyrophosphate positive electrode material. Although this technology uses a ball milling method to reduce the use of solvents, the preparation of its precursor is still a physical mixing process. In the subsequent sintering process, a large amount of CO2, CO and H2O will still volatilize, which makes the burn-out rate of the reaction high, which has an adverse effect on industrial production.
[0004] Patent application CN116404140A discloses a multi-element trace co-doped lithium iron phosphate / carbon composite positive electrode material, the general formula is: Li 1-xM x Fe 1-y TM y P 1-z S z O4 / C, 0 < x ≤ 0.05, 0 < y ≤ 0.05, 0 < z ≤ 0.05, where M is sodium and potassium, TM is two or more of aluminum, calcium, copper, chromium, magnesium, molybdenum, nickel, zinc, tin, and the carbon content is 1.5 - 4.5 wt%; the median particle size of the material is 2 - 6 μm, and the tapped density of the material is 1.25 - 1.4 g / cm 3 。This technology first grinds the iron source, phosphorus source and carbon source to obtain an intermediate product, then adds doping elements and continues ball milling, and finally calcines. However, this technology still has deficiencies such as complex processes: First, the two-step ball milling process involves multiple steps of physical and mechanical treatment, which not only increases the complexity of the operation but also may affect the consistency and stability of the product. At the same time, there are difficulties in particle size control. Although the median particle size of this technology is controlled within the range of 2 - 6 μm, accurately controlling the particle size distribution in actual operation is still a challenge. The non-uniformity of the particle size may lead to inconsistent battery performance and affect the overall performance of the battery. For the optimization of the tapped density, the tapped density of the material is between 1.25 - 1.4 g / cm 3 , and a lower value may affect the volumetric energy density of the material. In the process of trace multi-element doping, how to maintain a high tapped density while maintaining other electrochemical properties is a technical problem that needs to be overcome.
[0005] In view of these shortcomings, it is particularly important to explore new synthesis strategies to optimize the preparation process of iron-based phosphate sodium-ion cathode materials. Summary of the Invention
[0006] The purpose of the present invention is to provide an iron-based phosphate sodium-ion cathode material, its preparation method and application, specifically Na x Fe x-1 M y (PO4) x-2 P2O7 / C (x = 2 - 5, y = 0.002 - 0.1, M represents the doping element). The raw material utilization rate of this process is high, the burn-off rate of the reaction is low, the cost is low, the impurity content of the product is low and stable, and the obtained material shows excellent electrochemical performance when applied to sodium-ion batteries and can be used for industrial production.
[0007] The purpose of the present invention can be achieved by the following technical solutions: A preparation method of an iron-based phosphate sodium-ion cathode material, comprising the following steps:
[0008] (1) First, dissolve the iron source containing +2 valence and +3 valence and the phosphorus source containing sodium in deionized water respectively, mix them evenly, control the pH of the reaction to be 2-4, heat to 60-90° C. and react for 2-4 hours, centrifuge and dry the mixed solution after the reaction to obtain a powder precursor;
[0009] aF 2+ +bFe 3+ +xNa + +zPO4 3- +P2O7 4- →Na x Fe a+b (PO4) z P2O7
[0010] (2) mechanically mixing the precursor, sodium source, carbon source, dopant and solvent by ball milling or sand milling, and after completion, separating solid particles by centrifugation, and vacuum drying the obtained solid at 60-80° C. for 10-16 hours;
[0011] (3) The mechanically mixed product obtained in step (2) is first calcined at 250-350° C. for 3-6 h in an inert atmosphere or a hydrogen-argon mixed atmosphere, then sintered at 450-550° C. for 10-12 h, and naturally cooled to room temperature to obtain an iron-based phosphate sodium ion positive electrode material.
[0012] Furthermore, the iron source and the phosphorus source in step (1) are in a molar ratio of iron element to phosphorus element of c:c+1 (c=1-4), that is, the above formula a+b:z+2=(1-4):(2-5).
[0013] Furthermore, when ball milling is used in step (2), the ball milling is continued at a rotation speed of 300 to 500 rpm for 10 to 16 hours; when sand milling is used, the sand milling is continued at a rotation speed of 600 to 1000 rpm for 2 to 6 hours.
[0014] Furthermore, the iron-based sodium phosphate positive electrode material obtained in step (3) has the general formula: Na x Fe x-1 M y (PO4) x- 2P2O7 / C, where x = 2 to 5, y = 0.002 to 0.1, and M represents the doping element;
[0015] And, Na x Fe x-1 M y (PO4) x-2 The mass ratio of P2O7 to the carbon coating layer is 97-90:3-10.
[0016] Furthermore, the iron source in step (1) is at least two of ferric nitrate, ferrous nitrate, ferric chloride, ferrous chloride, ferrous sulfate, ferrous sulfate, ammonium ferrous sulfate, ferric citrate, and ferric dihydrogen phosphate;
[0017] The phosphorus source is at least one of sodium dihydrogen phosphate, sodium pyrophosphate, disodium hydrogen phosphate, disodium dihydrogen pyrophosphate, and sodium phosphate.
[0018] Furthermore, the sodium source in step (2) is at least one of sodium carbonate, sodium hydroxide, sodium pyrophosphate, disodium dihydrogen pyrophosphate, sodium oxalate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, sodium chloride, and sodium acetate;
[0019] The carbon source is at least one of glucose, sucrose, starch, citric acid, ascorbic acid, oxalic acid and polyvinyl alcohol.
[0020] Furthermore, the dopant in step (2) is at least one of titanium dioxide, copper oxide, copper hydroxide, manganese acetate, calcium hydroxide, zirconium oxide, aluminum hydroxide, and nickel nitrate, and the molar ratio of the added amount of the dopant to the theoretical product is 0.2 to 1:100.
[0021] Furthermore, the solvent used in the mechanical mixing in step (2) is at least one of ethanol, acetone, propanol and deionized water.
[0022] The invention also provides an iron-based sodium phosphate positive electrode material prepared by the method.
[0023] The present invention also provides a use of an iron-based phosphate sodium ion positive electrode material in preparing a positive electrode material for a sodium ion battery.
[0024] The present invention also includes using the iron-based phosphate sodium ion positive electrode material to prepare the positive electrode of the sodium ion battery, and testing its electrochemical performance.
[0025] Specifically, the iron-based phosphate sodium ion positive electrode material is uniformly mixed with a conductive agent and a binder, and then the slurry is coated on an aluminum foil, and the aluminum foil is placed in a vacuum oven for drying. The dried foil is cut into circular electrode sheets of a suitable diameter for making sodium ion button batteries.
[0026] Preferably, the Na prepared by the present invention x Fe x-1 M y (PO4) x-2P2O7 / C material, conductive carbon black, and PVDF binder were weighed in a mass ratio of 8:1:1. The positive electrode material and the conductive agent Super-P were weighed in a mass ratio of 8:1. After mixing evenly in a mortar, they were placed in an appropriate amount of NMP solvent with the binder PVDF and stirred to form a homogeneous slurry. The slurry was evenly coated on the Al foil current collector with a scraper. After drying, it was cut as the positive electrode, the sodium sheet was used as the negative electrode, and the electrolyte was 1M NaFP6 EC-DEC@5% FEC (1:1, V / V). Sodium button cells were prepared to test their electrochemical properties.
[0027] Compared with the prior art, the present invention has the following characteristics:
[0028] (1) The present invention prepares a precursor containing three elements: iron, phosphorus and sodium through a simple precipitation reaction. Among them, the iron element adopts two different valence states in the present invention. This diversity makes the iron-phosphorus ratio adjustable, providing flexibility for preparing precursors with different needs. The addition of phosphorus, as part of the precipitation reaction, helps to stabilize the generated precursor structure and provide a basis for the stability and electrochemical properties of the final product. The addition of phosphorus can also effectively promote the precipitation reaction, ensure the completeness and thoroughness of the reaction, thereby improving the overall production efficiency. At the same time, the synergistic effect of iron and phosphorus can ensure the preparation of precursors with different iron-phosphorus ratios, so that various iron-based phosphate sodium ion positive electrode materials can be obtained by only adding a sodium source in the subsequent ball milling and sintering steps, which simplifies the production process and greatly improves the production efficiency.
[0029] (2) The method of the present invention has a high raw material utilization rate. The key to reducing the sintering loss rate lies in the preparation of the precursor, which contains iron and phosphorus Na x Fe x-1 M y (PO4) x-2 The two key elements required for P2O7 / C materials do not contain volatile groups such as NH4 + and CO3 2- , which can minimize the loss of raw materials in the subsequent calcination process. The loss on ignition rate of the reaction during the sintering process of the present invention can be as low as 3.16% (such as Example 1), which is much lower than the 46.5% of the traditional FeC2O4 solution (patent CN115881948A). At the same time, the reactants of the method of the present invention are easy to obtain, the synthesis process is green, environmentally friendly, safe, and low-cost, the product has a low and stable impurity content, and the obtained material exhibits excellent electrochemical properties when applied to sodium ion batteries and can be used for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron microscope (SEM) image of the sample prepared in Example 1.
[0031] Figure 2 This is the X-ray diffraction (XRD) spectrum of the sample prepared in Example 1.
[0032] Figure 3 The 0.1C rate charge and discharge curve of the sodium ion button battery assembled from the sample prepared in Example 1.
[0033] Figure 4 This is a scanning electron microscope (SEM) image of the sample prepared in Example 2.
[0034] Figure 5 This is the X-ray diffraction (XRD) spectrum of the sample prepared in Example 2.
[0035] Figure 6 The 0.1C rate charge and discharge curve of the sodium ion button battery assembled from the sample prepared in Example 2. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following specific embodiments or drawings are used to illustrate the present invention, but are not used to limit the scope of the present invention.
[0037] Example 1
[0038] An iron-based phosphate sodium ion positive electrode material Na2FeTi 0.01 P2O7 / C, i.e. Na x Fe x-1 M y (PO4) x-2 The preparation of P2O7 / C (x=2, y=0.01) comprises the following steps:
[0039] (1) Na4P2O7, FeSO4 and Fe2(SO4)3 are weighed in a ratio of 1:2 between the molar ratio of iron and phosphorus, and dissolved in deionized water respectively. After being fully dissolved, the Na4P2O7 solution is slowly added to the solution of ferrous sulfate and ferric sulfate under stirring, and the pH of the reaction is controlled to be 2-4. The mixture is heated to 90°C for 3 hours. After the reaction is completed and cooled to room temperature, the product is separated and dried to obtain a dry precursor.
[0040] (2) Weigh the precursor obtained in step (1) and disodium hydrogen phosphate so that the molar ratio of Na:Fe:P is 2:1:2, and weigh the doping compound TiO2 at a molar ratio of 1:100 to the theoretical product. Add glucose as a carbon coating agent with a mass fraction of 10% of the total mass of the theoretical product, select anhydrous ethanol as a solvent and add it to a ball mill together with all the above solid components, add an appropriate amount of zirconium beads, place the ball mill symmetrically in a planetary ball mill, and ball mill at a speed of 300 rpm for 12 hours. After separation, the obtained solid is vacuum dried at 60°C for 12 hours.
[0041] (3) The ball-milled product was first calcined at 350°C for 3 h in an argon atmosphere, then sintered at 550°C for 12 h, and naturally cooled to room temperature to obtain Na2FeTi 0.01 P2O7 / C, i.e. Na x Fe x-1 M y (PO4) x-2 P2O7 / C (x=2, y=0.01).
[0042] (4) The target product prepared above is used as the positive electrode active material, and it is weighed with the conductive agent and the binder according to the mass ratio of active material, conductive agent and binder of 8:1:1. First weigh 240 mg of active material and 30 mg of Super-P conductive agent, mix them in a mortar for 10 minutes, and mix them evenly. In a 5 mL beaker, weigh 600 mg of 5% PVDF solution, add the mixed powder to the beaker, add 3 drops of NMP, seal the beaker with plastic wrap and sealing film, place it on a magnetic stirring table and stir with a stirrer for 4 hours to allow the components to be fully mixed. The slurry is spread on aluminum foil, vacuum dried at 120°C for 12 hours, and dried and cut into round electrode sheets to obtain sodium ion battery positive electrode sheets for button batteries.
[0043] (5) The above electrode sheet was used as the positive electrode, the sodium sheet was used as the negative electrode, and the electrolyte was 1M NaPF6 EC-DEC@5%FEC (1:1, V / V). The positive electrode sheet, separator, sodium sheet, gasket, and spring were placed in the order of assembling a CR2032 button battery. The packaged battery was left to stand for 24 hours so that the electrodes were fully infiltrated by the electrolyte for subsequent electrochemical performance testing.
[0044] Figure 1 This is a scanning electron microscope (SEM) image of the sample prepared in Example 1. It can be seen from the figure that the sample particles are evenly distributed, and the primary particle size is distributed in the range of 200 to 500 μm. The smaller size is conducive to the rapid transmission of sodium ions and has a positive effect on improving the electrochemical performance.
[0045] Figure 2This is the X-ray diffraction (XRD) spectrum of the sample prepared in Example 1. It can be seen from the figure that the diffraction peak of the sample strictly corresponds to the PDF standard card data, indicating that the Na2FeP2O7 positive electrode material has been successfully synthesized. At the same time, the Ti element will not introduce other phases into the raw materials.
[0046] Figure 3 The 0.1C rate charge-discharge curve of the sodium ion button battery assembled from the sample prepared in Example 1 shows that Na2FeTi 0.01 P2O7 / C has a current density of 95.6 mAh g at a current density of 0.1C. -1 The discharge capacity is the theoretical capacity (97 mAh g -1 ), indicating that the sodium ion positive electrode material prepared by the process of the present invention has excellent electrochemical properties.
[0047] Comparative Example 1
[0048] In order to reflect the advantages of the present invention, the same target product Na2FeTi as in Example 1 was prepared by a conventional solid phase method. 0.01 P2O7 / C, i.e. Na x Fe x-1 M y (PO4) x-2 P2O7 / C (x=2, y=0.01).
[0049] At present, the traditional solid phase method for preparing Na2FeP2O7 usually uses ferrous oxalate, diammonium hydrogen phosphate, and sodium carbonate as iron sources, phosphorus sources, and sodium sources. Therefore, the above three raw materials are weighed to make the molar ratio of Na:Fe:P = 2:1:2, and the doping compound TiO2 with a molar amount of 1% of the theoretical product is weighed, and then glucose with a mass fraction of 10% of the theoretical product is added as a carbon coating agent. Anhydrous ethanol is selected as a solvent and added to a ball mill together with all the above raw materials, and the ball mill is carried out at a speed of 300rpm for 12h. After separation, the obtained solid is vacuum dried at 60℃ for 12h.
[0050] The ball-milled product was first calcined at 350 °C for 3 h in an argon atmosphere, then sintered at 550 °C for 12 h, and naturally cooled to room temperature to obtain Na2FeTi 0.01 P2O7 / C. A button cell was prepared according to the method of steps (4)-(5) of Example 1.
[0051] Example 2
[0052] An iron-based phosphate sodium ion positive electrode material Na4Fe3Al 0.002 (PO4)2P2O7 / C, i.e. Na x Fe x-1 M y (PO4)x- The preparation of 2P2O7 / C (x=4, y=0.002) comprises the following steps:
[0053] (1) Weigh ferrous sulfate and ferrous sulfate, sodium pyrophosphate, and disodium hydrogen phosphate in a ratio of 3:4 in molar ratio of iron to phosphorus, and dissolve them in deionized water respectively. After they are fully dissolved, slowly add sodium pyrophosphate solution and disodium hydrogen phosphate solution to the mixed solution of ferrous sulfate and ferrous sulfate under stirring, and control the pH of the reaction to be 2-4. Heat to 70°C for 3h, and after the reaction is completed and cooled to room temperature, separate the product and dry it to obtain a dry precursor.
[0054] (2) Weigh the precursor and sodium carbonate obtained in step (1) to make the molar ratio of Na:Fe:P = 4:3:4. At the same time, weigh 0.2% of the theoretical product molar amount of the doping compound Al(OH)3, and then add 10% of the theoretical product mass fraction of ascorbic acid as a carbon coating agent, select anhydrous ethanol as a solvent and add it to a sand mill together with all the above solid components, add an appropriate amount of zirconium beads, set the speed to 600 rpm, and perform sand milling for 4 hours. After separation, the obtained solid is vacuum dried at 60°C for 12 hours.
[0055] (3) The sand-milled product was first calcined at 300° C. for 6 h in an argon atmosphere, then sintered at 500° C. for 10 h, and naturally cooled to room temperature to obtain the Na4Fe3Al 0.002 (PO4)2P2O7 / C, i.e. Na x Fe x-1 M y (PO4) x-2 P2O7 / C (x=4, y=0.002).
[0056] (4) The electrode sheet preparation and electrochemical testing are similar to those in Example 1.
[0057] Figure 4 This is a scanning electron microscope (SEM) image of the sample prepared in Example 2. It can be seen from the image that the particles agglomerated with each other to form larger irregular particles. The primary particle size of the sample is distributed around 500 μm. Smaller particle size is conducive to the penetration of electrolyte and produces better electrochemical performance.
[0058] Figure 5 This is the X-ray diffraction (XRD) spectrum of the sample prepared in Example 2. The diffraction peaks match well with the standard card, indicating that the Na4Fe3(PO4)2P2O7 material has been successfully synthesized. In addition, no other impurity peaks were observed, indicating that the material prepared by the process of the present invention has a higher purity.
[0059] Figure 6The 0.1C rate charge-discharge curve of the sodium ion button battery assembled from the sample prepared in Example 2. It can be seen from the figure that the sample has a current density of 123 mAh g at 0.1C. -1 The discharge capacity is the theoretical capacity (129 mAh g -1 ) is 95.3% and the first coulombic efficiency is as high as 96.5%, indicating that it has excellent electrochemical performance.
[0060] Comparative Example 2
[0061] In order to reflect the advantages of the present invention, the same target product Na4Fe3Al2O3 as in Example 2 was prepared by a conventional solid phase method. 0.002 (PO4)2P2O7 / C, i.e. Na x Fe x-1 M y (PO4) x-2 P2O7 / C (x=4, y=0.002).
[0062] The traditional solid phase method for preparing Na4Fe3(PO4)2P2O7 usually uses ferrous oxalate, diammonium phosphate, and sodium carbonate as iron, phosphorus, and sodium sources. Therefore, ferrous oxalate, diammonium phosphate, and sodium carbonate are weighed to make the molar ratio of Na:Fe:P = 4:3:4, and 0.2% of the theoretical product molar amount of the doping compound Al(OH)3 is weighed at the same time, and then 10% of the theoretical product mass fraction of glucose is added as a carbon coating agent, and anhydrous ethanol is selected as the solvent and added to the sand mill together with all the above solid components, and an appropriate amount of zirconium beads is added, and the speed is set to 600rpm, and the sand milling is carried out for 4 hours. After separation, the obtained solid is vacuum dried at 60°C for 12 hours.
[0063] The milled product was first calcined at 300 °C for 6 h in an argon atmosphere, then sintered at 500 °C for 10 h, and naturally cooled to room temperature to obtain Na4Fe3Al 0.002 (PO4)2P2O7 / C. A button cell was prepared according to the method of steps (4)-(5) of Example 1.
[0064] Example 3
[0065] A preparation method of an iron-based sodium phosphate positive electrode material comprises the following steps:
[0066] (1) Weigh ferrous sulfate and ferric nitrate, disodium dihydrogen pyrophosphate, and sodium dihydrogen phosphate according to the molar ratio of Fe:P=2:3, dissolve them in deionized water respectively, and slowly add disodium dihydrogen pyrophosphate solution and sodium dihydrogen phosphate solution to the mixed solution of ferrous nitrate and ferrous sulfate under stirring after they are fully dissolved, and control the pH of the reaction to be 2-4. Heat to 60°C for 3h, cool to room temperature after the reaction is completed, separate the product, and dry it to obtain a dry precursor.
[0067] (2) Weigh the precursor and sodium oxalate obtained in step (1) to make the molar ratio of Na:Fe:P = 3:2:3. At the same time, weigh 0.4% of the theoretical product molar amount of the doping compound ZrO2, and then add 10% of the theoretical product mass fraction of citric acid as a carbon coating agent, propanol as a solvent to the ball mill, select anhydrous ethanol as a solvent and add it to the ball mill together with all the above solid components, and add an appropriate amount of zirconium beads, symmetrically place the ball mill in a planetary ball mill, and ball mill at a speed of 350 rpm for 14 hours. After separation, the obtained solid is vacuum dried at 60°C for 12 hours.
[0068] (3) The ball-milled product was first calcined at 350 °C for 6 h in an argon atmosphere, then sintered at 550 °C for 12 h, and naturally cooled to room temperature to obtain the desired sample Na3Fe2Zr 0.004 PO4P2O7 / C, namely Na x Fe x-1 M y (PO4) x-2 P2O7 / C (x=3, y=0.004).
[0069] (4) The electrode sheet preparation and electrochemical testing are similar to those in Example 1.
[0070] Example 4
[0071] A preparation method of an iron-based sodium phosphate positive electrode material comprises the following steps:
[0072] (1) Weigh ferrous chloride, ferric chloride and disodium hydrogen phosphate in a molar ratio of Fe:P=4:5, dissolve them in deionized water respectively, and slowly add the disodium hydrogen phosphate solution to the ferric chloride and ferrous chloride solutions under stirring after they are fully dissolved, and control the pH of the reaction to be 2-4. Heat to 80°C for 3h, cool to room temperature after the reaction is completed, separate the product, and dry it to obtain a dry precursor.
[0073] (2) Weigh the precursor and sodium hydroxide obtained in step (1) to make the molar ratio of Na:Fe:P = 5:4:5. At the same time, weigh 0.6% of the theoretical product molar amount of the doping compound nickel nitrate, and then add 10% of the theoretical product mass fraction of polyvinyl alcohol as a carbon coating agent, select acetone as a solvent and add all the above solid components into a sand mill, add an appropriate amount of zirconium beads, set the speed to 800 rpm, and perform sand milling for 3 hours. After separation, the obtained solid is vacuum dried at 60°C for 12 hours.
[0074] (3) The milled product was first calcined at 320 °C for 6 h in an argon atmosphere, then sintered at 520 °C for 10 h, and naturally cooled to room temperature to obtain the desired sample Na5Fe4Ni 0.006(PO4)3P2O7 / C, i.e. Na x Fe x-1 M y (PO4) x-2 P2O7 / C (x=5, y=0.006).
[0075] (4) The electrode sheet preparation and electrochemical testing are similar to those in Example 1.
[0076] Table 1: Electrochemical properties of the materials obtained in each example
[0077]
[0078] As shown in Table 1, Example 1 and Comparative Example 1 prepared the same material Na2FeTi 0.01 The discharge capacity of P2O7 / C, Example 1 at 0.1C is 95.6 mAh g -1 , is the theoretical capacity (97 mAh g -1 ) is 98.5%, which is higher than 83.3 mAhg in Comparative Example 1 -1 Moreover, the capacity retention rate of Example 1 after 400 cycles at 1C and 1000 long cycles at a current density of 2C is also better than that of Comparative Example 1.
[0079] Example 1 Chemical reactions occurring during sintering:
[0080] Fe2P2O7+2Na2HPO4=2Na2FeP2O7+H2O
[0081] Only a small amount of water is lost in the reaction during this process, and the loss on ignition rate of the reaction is only 3.16%. The specific calculation method of the loss on ignition rate is: (mass before sintering reaction - mass after sintering reaction) / mass before sintering reaction × 100%. If there is 1 mol of Fe2P2O7 and 2 mol of Na2HPO4 before the reaction, then the mass is 570g. Assuming that the reaction is fully carried out and there is no loss, then the substance left after the reaction is 2 mol of Na2FeP2O7, and its mass is 552g. The theoretical loss on ignition rate is (570-552) / 570×100%=3.16%.
[0082] The chemical reactions occurring during the sintering process of Comparative Example 1 are as follows:
[0083] FeC2O4·2H2O+Na2CO3+2(NH4)2HPO4=Na2FeP2O7+2CO2+CO+4NH3+5H2O
[0084] In this process, a large amount of gas and water are lost in the reaction. Similarly, the burning rate of the reaction is 49.86%. Example 2 and Comparative Example 2 belong to different preparation processes of the same material. The discharge capacity of Example 2 at 0.1C is 123.3 mAh g -1 , is the theoretical capacity (129 mAh g -1 ), and the first coulombic efficiency and cycle performance of Example 2 are significantly improved compared with those of Comparative Example 2. Therefore, the sodium ion positive electrode material prepared by the new process not only has advantages in electrochemical performance, but also has high raw material utilization rate, and the burn-off rate of the reaction is greatly reduced compared with the traditional solid phase method.
[0085] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
[0086] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing an iron-based sodium phosphate positive electrode material, characterized in that: The following steps are involved: (1) First, dissolve the iron source containing +2 valence and +3 valence and the phosphorus source containing sodium in deionized water respectively, mix them evenly, control the pH of the reaction to be 2-4, heat to 60-90° C. and react for 2-4 hours, centrifuge and dry the mixed solution after the reaction to obtain a powder precursor; aFe 2+ +bFe 3+ +xNa + +zPO4 3- +P2O7 4- →Na x Fe a+b (PO4) z P2O7 (2) mechanically mixing the precursor, sodium source, carbon source, dopant and solvent by ball milling or sand milling, and after completion, separating solid particles by centrifugation, and vacuum drying the obtained solid at 60-80° C. for 10-16 h; (3) The mechanically mixed product obtained in step (2) is first calcined at 250-350° C. for 3-6 h in an inert atmosphere or a hydrogen-argon mixed atmosphere, then sintered at 450-550° C. for 10-12 h, and naturally cooled to room temperature to obtain an iron-based phosphate sodium ion positive electrode material.
2. The method for preparing an iron-based sodium phosphate positive electrode material according to claim 1, characterized in that: The iron source and the phosphorus source in step (1) are in a molar ratio of iron element to phosphorus element c:c+1 (c=1-4), that is, the above formula a+b:z+2=(1-4):(2-5).
3. The method for preparing an iron-based sodium phosphate positive electrode material according to claim 1, characterized in that: When the ball milling method is adopted in step (2), the ball milling is continued for 10 to 16 hours at a rotation speed of 300 to 500 rpm; When sand milling is used, the sand milling is performed at a rotation speed of 600 to 1000 rpm for 2 to 6 hours.
4. The method for preparing an iron-based sodium phosphate positive electrode material according to claim 1, characterized in that: The general formula of the iron-based sodium phosphate positive electrode material obtained in step (3) is: Na x Fe x-1 M y (PO4) x-2 P2O7 / C (x=2-5, y=0.002-0.1, M represents doping element) x Fe x-1 M y (PO4) x-2 The mass ratio of P2O7 to the carbon coating layer is 97-90:3-10.
5. The method for preparing an iron-based sodium phosphate positive electrode material according to claim 1, characterized in that: The iron source in step (1) is at least two of ferric nitrate, ferrous nitrate, ferric chloride, ferrous chloride, ferrous sulfate, ferrous sulfate, ammonium ferrous sulfate, ferric citrate, and ferric dihydrogen phosphate; The phosphorus source is at least one of sodium dihydrogen phosphate, sodium pyrophosphate, disodium hydrogen phosphate, disodium dihydrogen pyrophosphate, and sodium phosphate.
6. The method for preparing an iron-based sodium phosphate positive electrode material according to claim 1, characterized in that: The sodium source in step (2) is at least one of sodium carbonate, sodium hydroxide, sodium pyrophosphate, disodium dihydrogen pyrophosphate, sodium oxalate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, sodium chloride, and sodium acetate; The carbon source is at least one of glucose, sucrose, starch, citric acid, ascorbic acid, oxalic acid and polyvinyl alcohol.
7. The method for preparing an iron-based sodium phosphate positive electrode material according to claim 1, characterized in that: The dopant in step (2) is at least one of titanium dioxide, copper oxide, copper hydroxide, manganese acetate, calcium hydroxide, zirconium oxide, aluminum hydroxide and nickel nitrate, and the molar ratio of the added amount of the dopant to the theoretical product is 0.2 to 1:
100.
8. The method for preparing an iron-based sodium phosphate positive electrode material according to claim 1, characterized in that: The solvent used in the mechanical mixing in step (2) is at least one of ethanol, acetone, propanol and deionized water.
9. An iron-based sodium phosphate positive electrode material prepared by the method described in any one of claims 1 to 8.
10. Use of an iron-based phosphate sodium ion positive electrode material according to claim 9 in preparing a positive electrode material for a sodium ion battery.
Citation Information
Patent Citations
Preparation method and application of ferric sodium pyrophosphate positive electrode material
CN117819512A
Preparation method of doped modified sodium ferric pyrophosphate positive electrode material
CN115133023A
Preparation method of high-performance sodium ion battery positive electrode material Na4Fe3 (PO4) 2P2O7
CN117585658A
Preparation method of high-compaction-density polyphosphoryl sodium-ion battery positive electrode material
CN117790760A
High-purity iron-based polyanion compound as well as preparation and application thereof
CN117886287A
Cited By
Sodium-ion battery positive electrode material based on double / multi-iron-source polyanions, and preparation method and application of sodium-ion battery positive electrode material
CN121097071A
Low-band-gap ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof
CN121376950A
Iron-manganese-based mixed phosphate micro-nano secondary sphere as well as preparation method and application thereof
CN121698318A